Determination of Medical Students’ Perception on Disaster Awareness - Bilge DELİBALTA; Abdul Samet ŞAHİN; Enes BULUT; Berkay YILDIZ; Abdülkadir GÜNDÜZ (Bezmiâlem Science)
Objective: Medical students and general practitioners have a vital role in disasters both in the “preparedness and mitigation” and “response and recovery” phases. To prepare students management of disasters as health professionals, the level of disaster preparedness perceptions of the students should be evaluated. So, the undergraduate medical curriculum can be structured to ensure the readiness of the students for disaster. The aim of the study was to determine the level of disaster preparedness perception of medical students. Methods: This descriptive study was conducted in the Faculty of Medicine of a state university. The population of the study consisted of students studying in the fourth, fifth and sixth grades of the medical faculty which had a training on disaster module in the fifth year. The study was completed with the participation of 288 students. In the data collection process, “personal information form” and the “disaster preparedness perception scale of personnel working in prehospital emergency health services” were used. Results: It was found that exposure to disasters, presence of individuals exposed to disasters in the family and environment, participation in disaster exercises, receiving disaster training, willingness to volunteer in disasters, the level of participants' perception of themselves as prepared for disasters, the level of perception of the disaster risk of the region of residence, were effective on the mean total score of the scale. Conclusion: Disaster preparedness perception can be seen as a first step toward competency in disaster management in medical students. Conducting simulation-based well-structured training modules is recommended to improve the disaster preparedness perceptions of the students. Further studies are needed to evaluate the effect of simulation-based training in disaster management.